DEVELOPMENT OF READING SKILLS OF STUDENTS - Gulnoza Ibragimjanova (Western European Studies, 2024)
At present, a new education system is being established in Uzbekistan. There is a change in the educational paradigm, a new content of education is being introduced. The task of improving, developing and optimizing the methods of teaching foreign languages has always been and remains one of the urgent problems of education in Uzbekistan. The development of reading skills in B1 level students attracts close attention of researchers and educatorspractitioners. Learning a foreign language has become a requirement of the time. One of the main goals of teaching English at the level of primary general education is the formation of the ability to communicate in a foreign language, taking into account the speech capabilities and needs of younger students. Reading is one of the main types of speech activity. It can be both a goal and a means of learning. Thanks to reading, a person joins the cultural and scientific achievements of mankind, gets acquainted with the art and life of other peoples. The process of reading has a huge impact on the formation of personality. While reading, students' active and passive vocabulary is enriched
Keywords: reading skills; development; vocabulary